Un musée à ciel ouvert ? Anthropologie du patrimoine végétal protestant dans le Moyen Poitou - Jérôme Lamy (Diasporas: Circulations, Migrations, Histoire)
The pine tree is associated, in the Moyen Poitou, with the history of Protestantism. A collective myth associated this tree to friendly Protestants houses during the “Desert.” This article deals with the persistence of this botanical memory. An ethnography study and a historical analysis of the recent re-emergence of the Protestant pine tree, in the field of local learning, restores the anchor of this tree in the contemporary heritage regime.